2021
DOI: 10.5435/jaaos-d-21-00190
|View full text |Cite
|
Sign up to set email alerts
|

Klippel-Feil Syndrome: Pathogenesis, Diagnosis, and Management

Abstract: Klippel-Feil syndrome (KFS), or congenital fusion of the cervical vertebrae, has been thought to be an extremely rare diagnosis. However, recent literature suggests an increased prevalence, with a high proportion of asymptomatic individuals. Occurring as a sporadic mutation or associated with several genes, the pathogenesis involves failure of cervical somite segmentation and differentiation during embryogenesis. Most commonly, the C2-C3 and C5-C6 levels are involved. KFS is associated with other orthopaedic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 43 publications
1
21
0
4
Order By: Relevance
“…C2-3 congenital fusion is often associated with AAD, which results in neurological dysfunction and requires reduction and fixation to relieve ventral cervical cord compression [ 10 , 15 ]. Pedicle screws insertion is the commonly used technique for C2 fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C2-3 congenital fusion is often associated with AAD, which results in neurological dysfunction and requires reduction and fixation to relieve ventral cervical cord compression [ 10 , 15 ]. Pedicle screws insertion is the commonly used technique for C2 fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Common symptoms of the syndrome are short neck, low hairline, and limited head movement [ 7 ]. C2-3 is a common fusion zone that is often associated with the C0-1 fusion zone, which increases the stress on the atlantoaxial joint, leading to atlantoaxial dislocation (AAD) [ 10 , 15 ]. Therefore, the stabilization of the atlantoaxial joint by fixation is the primary treatment strategy for patients with C2-3 fusion and AAD [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion criteria were: patients who had undergone previous surgery on the cervical spine (either anterior or posterior); those with no active motion of the target level on dynamic studies; those with increased anteroposterior translation of the target level by > 3 mm on dynamic studies; those with a fused or very narrow disc levels (central < 3 mm); severe segmental kyphosis of the involved disc level by > 3°; those with neck pain without radicular symptoms; evidence of myelopathy; infection; metabolic and bone diseases (such as osteoporosis and severe osteopenia); trauma or neoplasia of the cervical spine; a spinal anomaly (such as Klippel Feil syndrome, 10 ankylosing spondylitis, 11 or ossification of the posterior longitudinal ligament); 12 evidence of a psychiatric disorder; those who did not speak Dutch; or those who planned to leave the country in the year after inclusion. 9…”
Section: Methodsmentioning
confidence: 99%
“…A recent study suggested that Klippel-Feil syndrome was present in as many as 1 in 172 births [15]. Nonsurgical management for Klippel-Feil syndrome focuses on long-term pain management [16], whereas surgery involves posterior cervical fusion. The correction of congenital scoliosis is often considered in conjunction with the surgical treatment of Klippel-Feil syndrome [16].…”
Section: Vertebral Abnormalitiesmentioning
confidence: 99%